(untitled) (Web of Teachers: Inderscience Research, 2024)
The article talks about the monument to Akhsikent, one of the ancient cities in the Fergana Valley. “Futuh al-buldon” by Al-Balozuri (d. 892), “Masolik val- mamalik” by Istakhri (850-957), “Ahsan at-taqasim fi ma’rifatil-aqalim” by Shamsiddin al-Muqaddasiy (947-990) , “Al-Masalik val-mamalik” by Ibn Khurdodbek (820-912), Hudud al-alam, Mujam al-buldon by Yaqut al-Hamawi (1179-1229), “Nuzha al-Mushtaq” by Abu Ubaydullah al-Idrisi (1100-1165), “Surat al-Ard” by Ibn Hawqal (d. 976) narrated about information the city. Also, the researches carried out in Akhsikent by archeologists such as N.Veselovsky, I.Kastane, M.Masson, Ya.Gulamov, A.Anorboev, Y.Kasimov, I.Ahrorov, A.Mohammadjonov in the end of the XIX and XX centuries and their results how compatibility was analyzed.